Concept of Aushadha Dharna (Tying Some Parts of Medicinal Herbs) in Ayurveda (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda is one of the oldest and most widely used traditional systems of medicine. The ancient knowledge of this traditional system of healing has yet to be fully explored. The confluence of rich information from several traditional medical systems might lead to new possibilities in the herbal drug development process. Apart from the various hurdles to the development of plant-based medicines, the lack of knowledge of the differences and similarities between the theoretical doctrines of these systems is the main obstacle to their convergence. In the ancient times, medicine has been closely related to science as well as religion and faith. Ancient civilization had developed different assessments of medicine. They believe that medicine was mythological, and diseases were ascribed mostly to the supernatural forces. The goal of this review paper is to highlight the ancient concept of use of medicine as on amulet, the core concepts of Ayurveda.